Atorvastatin Therapy Modulates Telomerase Activity in Patients Free of Atherosclerotic Cardiovascular Diseases - Strazhesko, Irina D.; Tkacheva, Olga N.; Akasheva, Dariga U.; Dudinskaya, Ekaterina N.; Plokhova, Ekaterina V.; Pykhtina, Valentina S.; Kruglikova, Anna S.; Kokshagina, Natalia V.; Sharashkina, Natalia V.; Agaltsov, Mikhail V.; Kashtanova, Daria A.; Vygodin, Vladimir A.; et al. (Frontiers in Pharmacology, 2016)
Background— Telomerase activity (TA) is considered as the biomarker for cardiovascular aging and cardiovascular diseases. Recent studies suggest a link between statins and telomere biology that may be explained by anti-inflammatory actions of statins and their positive effect on TA. Until now this effect has not been investigated in prospective randomized studies. We hypothesized that 12 months of atorvastatin therapy increased TA in peripheral blood mononuclear cells. Methods—In a randomized, placebo-controlled study 100 hypercholesterolemic patients, aged 35–75 years, free of known cardiovascular diseases and diabetes mellitus type 2 received 20 mg of atorvastatin daily or placebo for 12 months. TA was measured by quantitative polymerase chain reaction. Results—At study end 82 patients had sufficient peripheral blood mononuclear cells needed for longitudinal analysis. TA expressed as natural logarithms changed from 0.46±0.05 to 0.68±0.06 (p=0.004) in the atorvastatin group and from 0.67±0.06 to 0.60±0.07 (P=0.477) in the control group. In multiple regression analysis, atorvastatin therapy was the only independent predictor (p=0.05) of the changes in TA independently of markers of chronic inflammation and oxidative stress. Atorvastatin therapy was associated with increases in IL-6 within the normal range and a tendency towards reductionin blood urea. Conclusions—These initial observations suggest atorvastatin can act as telomerase activator and potentially as effective geroprotector.